Effect of anisodine with chlorpromazine on content of acetylcholine in some brain areas - HUANG Jun-hua; CHEN Zeng-xing; WANG Gui-lian (Acta Pharmacologica Sinica, 2016)
The effects of anisodine-HBr and chlorpromazine (CPZ) on the Ach content in some brain areas have been studied by both microbioassay on leech dorsal muscle and radioimmunoassay. The Ach content in the cerebral cortex and striatum was decreased after iv anisodine 3 mg/kg alone and in combination with CPZ 4 mg/kg, while the Ach content in the hippocampus remained the same as the control group. CPZ did not show any marked effect on the content of Ach in the brain areas studied except striatum. It is suggested that there is no correlation between the behavioral activity of animal and the content of Ach in the above mentioned brain areas.